Theoretical study of the elastic and thermodynamic properties of Pt₃Al with the L1₂ structure under high pressure - Wei, N.; Zhang, Ch.; Hou, S. (Condensed Matter Physics, 2015)
In this work, the elastic and thermodynamic properties of Pt₃Al under high pressure are investigated using density functional theory within the generalized gradient approximation. The results of bulk modulus and elastic constants at zero pressure are in good agreement with the available theoretical and experimental values. Under high pressure, all the elastic constants meet the corresponding mechanical stability criteria, meaning that Pt₃Al possesses mechanical stability. In addition, the elastic constants and elastic modulus increase linearly with the applied pressure. According to the Poisson's ratio ν and elastic modulus ratio (B/G), Pt₃Al alloy is found to be ductile, and higher pressure can significantly enhance the ductility. Those indicate that the elastic properties of Pt₃Al will be improved under high pressure. Through the quasi-harmonic Debye model, we first successfully report the variations of the Debye temperature ΘD, specific heats CP, thermal expansion coefficient α, and Grüneisen parameter γ under pressure range from 0 to 100 GPa and temperature range from 0 to 1000 K.